2022
DOI: 10.1186/s12913-022-07704-0
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey: knowledge, attitudes, and practices of self-medication in medical and pharmacy students

Abstract: Background Self-Medication is common practice worldwide in both developed and developing countries. Self-Medication is referred as self consumption of medication without consulting a physician for either diagnosis or treatment. This study aimed to assess the knowledge, attitudes and practices toward self-medication among medical and pharmacy students. Methods This cross-sectional study was conducted among medical and pharmacy students in Qassim uni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
3
4
0
2
Order By: Relevance
“…It was identified that about half of the students were using prescribed painkillers either differently than a doctor had advised or without a doctor's prescription. This is consistent with research by Alduraibi and Altowayan 16 in Saudi Arabia, who reported that the majority of…”
Section: Discussionsupporting
confidence: 93%
“…It was identified that about half of the students were using prescribed painkillers either differently than a doctor had advised or without a doctor's prescription. This is consistent with research by Alduraibi and Altowayan 16 in Saudi Arabia, who reported that the majority of…”
Section: Discussionsupporting
confidence: 93%
“…More than one-third of HCWs considered self-medication as a part of self-care and they felt they could diagnose different diseases by themselves. These findings are similar to a study from Saudi Arabia among medical and pharmacy students where most participants had good knowledge of self-medication [ 103 ]. However, physicians and pharmacists had better knowledge of self-medication in our study compared with nurses and other HCWs.…”
Section: Discussionsupporting
confidence: 89%
“…The data collection tool used in our survey was developed from previous studies combined with the considerable experience of the co-authors as well as observing local practices [ 55 , 103 , 110 , 113 , 114 , 139 ]. We have used this method before when developing context-specific data collection forms [ 101 , 131 , 140 , 141 , 142 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most respondents assume that antibiotics cannot be given for viral diseases because they are cured automatically, and these results are good when we compare them with the results of a research conducted in Saudi Arabia, where (21.40%) of respondents think that viral infections are cured automatically. Due to a lack of awareness of the differences between viral and bacterial diseases, some respondents prefer taking antibiotics to treat all infections rather than treating the underlying cause (Alduraibi & Altowayan, 2022;Lalithabai et al, 2022;Rahman et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The research result concluded that pharmacy students have superior knowledge of medication application than health sciences students. All health sciences students lacked the necessary mindset and application when it came to drug safety (Alduraibi & Altowayan, 2022;Wang et al, 2019;Lalithabai et al, 2022). The current study aims to determine students' knowledge about antibiotic utilization for upper respiratory tract infections in children.…”
Section: Introductionmentioning
confidence: 99%